2011
DOI: 10.1002/ptr.3626
|View full text |Cite
|
Sign up to set email alerts
|

The Sustained Influence of Short Term Exposure to a Proprietary Extract of North American Ginseng on the Hemopoietic Cells of the Bone Marrow, Spleen and Blood of Adult and Juvenile Mice

Abstract: This study assessed the influences of CVT-E002, a proprietary extract of North American ginseng, Panax quinquefolius (Afexa Life Sciences, Inc., Edmonton, AB, Canada), in vivo, on murine hemopoietic and immune cells when administered as a dietary additive. The extract was given daily to young, adult mice for a period of 4 weeks, immediately following which one group was euthanized and the hemopoietic and immune cells of their bone marrow, spleen and blood were assayed for CVT-E002-mediated alterations in any o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…AGRPS and AQ extracts are not antagonists of LPS because they have low stimulatory effect and also requires pretreatment before they can suppress LPS stimulation. The data from this study supports the reported CVT-E002 TM immunostimulatory [22,29,48,[59][60][61][62] and suppression of proinflammatory effects [21,63] under basal and induced proinflammatory conditions respectively. Therapies directed at the neutralization of proinflammatory mediators Fig.…”
Section: Discussionsupporting
confidence: 93%
“…AGRPS and AQ extracts are not antagonists of LPS because they have low stimulatory effect and also requires pretreatment before they can suppress LPS stimulation. The data from this study supports the reported CVT-E002 TM immunostimulatory [22,29,48,[59][60][61][62] and suppression of proinflammatory effects [21,63] under basal and induced proinflammatory conditions respectively. Therapies directed at the neutralization of proinflammatory mediators Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Similar meta-analysis [64–65] showed that Aidi injection could decrease the toxicity induced by navelbine and cisplatin (NP) or paclitaxel and cisplatin(TP) in NSCLC. Most studies showed that Astragalus, Eleutherococcus senticosus, and Ginseng might reduce the chemotherapy related toxicity through promoting hematopoiesis [6667] and relieving oxidative stress [6871]. These studies provide indirect evidence for the above conclusions.…”
Section: Discussionmentioning
confidence: 97%
“…AG's extract concentrate appeared to be a potential radiation countermeasure on human peripheral blood lymphocytes administered as a dietary supplement [42]. AG's extract concentrate had a dependable, positive quantitative effect on the lymphocytes and monocytes in mice [43]. AG increased the number of natural killer cells in mice spleen and bone marrow [44].…”
Section: Effects On the Immune Systemmentioning
confidence: 99%